Land use effects on the functional structure of aquatic insect communities in Neotropical streams. Issue 3 (3rd July 2017) - Gimenez, Barbara C. G.; Higuti, Janet
Abstract: Land use and occupation by human populations can cause many environmental changes in streams, which affect not only the number and abundance of species but also the biological characteristics or functional traits of the individuals. Here we investigated the influence of different land uses (agriculture and urbanization) on taxonomic and functional diversity of aquatic insects in drift samples from Neotropical streams. To this end, we used 2 diversity metrics: the Shannon-Wiener diversity index (H′) to quantify taxonomic diversity and Rao's quadratic entropy index (Q) to measure functional diversity. In addition, we analyzed the importance of environmental variables on functional traits composition. The high heterogeneity of habitats in rural streams contributed to the occurrence of sensitive taxa (i.e., specialist taxa), which mostly do not share the same categories of functional traits, providing higher functional diversity in these streams. Conversely, the impacts resulting from urbanization processes changed the abiotic variables and led to habitat simplification, favoring the dominance of tolerant (generalist) taxa, which share more traits, thus reducing the taxonomic and functional diversity in these sites. Assessing the functional diversity of aquatic insects under the influence of different land uses is of utmost importance to better understand the functioning of aquatic communities impacted by land use change.